Phase Ib/IIa study assessing the safety and efficacy of AL8326 monotherapy in patients with ≥3rd line small cell lung cancer (SCLC) treatment - Li, Xingya; Bi, Minghong; Su, Chunxia; Fang, Yong; WANG, Zibing; Yuan, Ying; Du, Xiuping; Lv, Tangfeng; Li, Yingyin (Journal of clinical oncology, 2023)
8585Background: AL8326 is a novel, orally administered, small molecule tyrosine kinase inhibitor (TKI). The primary objective of this Phase Ib/IIa study is to evaluate the safety and efficacy of AL8326 monotherapy in patients with ≥3rd line small cell lung cancer (SCLC) treatment. Methods: Patients with a diagnosis of small cell lung cancer either limited or extended stage requiring third or further line treatment were eligible for enrollment. The regimen was a 28-day cycle with oral AL8326 administered at 60 mg once per day via RECISIT1.1 evaluation until disease progression (PD), or intolerable toxicity or any other reason discontinuations. Results: At the cut-off date Nov 30, 2022, total n = 30 patients were enrolled. The objective response rate (ORR) was 20% (6/30) (4 confirmed). The disease control rate (DCR) was 56.7% (17/30). Median progression-free survival (PFS) was 3.65 months (95% CI: 1.9 - 5.5) and median overall survival (OS) was 10.42 months (95% CI: 5.4, NE). The median duration of response (DOR) was 5.6months. All 30 subjects had reported AE at least once. Common treatment emergent adverse events (TEAE) were similar to other TKI drug and included (incidence ≥20%): thyroid stimulating hormone (TSH) increase (46.67%), proteinuria (43.33%), weight loss (40.00%), hypertension (36.67%), thrombocytopenia (33.33%), diarrhea (33.33%), positive fecal occult blood (30.00%), hypercholesterolemia (26.67%), hypertriglyceridemia (26.67%), hand- foot syndrome (HFS) (20.00%), loss of appetite (20.00%). Most of these AEs were grade 1-2 (CTCAE V5.0). Conclusions: AL8326 has demonstrated acceptable tolerability and positive efficacy on small cell lung cancer treatment. A US Phase 2 (NCT05363280) study is ongoing and a phase 3 study is in preparation. Clinical trial information: NCT04890795.